Women's experiences of water immersion during labour and childbirth in a hospital setting in Ireland: A qualitative study. (May 2022) - Dado, Mariapia; Smith, Valerie; Barry, Paula
Abstract: Background: Water immersion during labour and birth has been acknowledged worldwide as a safe option for low-risk pregnant women. The extent of use of water immersion in the Republic of Ireland, however, is largely limited, as few maternity units have installed birthing pools. To explore women's experience of water immersion during labour and birth in a hospital setting in Ireland, a qualitative study was undertaken. Setting: A tertiary referral centre with an annual birth rate of over 8000 in Dublin, Ireland. Design: The study adopted a descriptive qualitative approach. Thematic analysis was undertaken to identify recurrent themes and patterns. Participants: Participants included nine women who had a water birth in the study site between February 2019 and November 2019. One-to-one, semi-structured interviews were used to collect data. Findings: Three main themes were identified: 'Waterbirth: keeping it normal in a hospital setting', 'Intimate experience' and 'An unknown, underestimated resource'. Women reported that water immersion helped them achieve a positive, more natural birth experience which enhanced maternal-infant bonding. Findings also showed that water immersion facilitated birth partners to be more actively involved in the birth process. However, the lack of information and accessibility to the birthing pool, created a sense of anxiety amongst women wishing to opt for this care option, leading to dissatisfaction with the current model of care/service provision. Key conclusions: Findings suggest that water immersion assists in preserving the physiological processes of birth even in a medicalised/hospital birth setting. Water immersion can be considered a valuable option for ensuring a positive childbirth experience for women and their birth partners. Implications for practice: To ensure waterbirth is a viable option for women in Ireland, greater engagement with and education on the advantages of water birth is required along with an exploration of other factors such as cost-effectiveness and heath professionals' views.